Pengaruh Persepsi Harga, Cita Rasa Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Rumah Makan Kuningan Hegarmukti - Setiani, Rijki Indah; Aming, Aming; Sopian, Ahmad; Anggoro, Thomas; Prasetya, Denny Dwi (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The culinary industry has become a global issue for business operators, offering promising opportunities, especially in today's rapidly developing world. Food has evolved into a culinary industry that not only provides taste but also fulfills socializing needs and aspirations. The tent industry is rapidly growing in Cikarang City. One small business in the food industry located in Central Cikarang, known as Warung Makan Kuningan, exemplifies this trend. The proliferation of food vendors in this city indicates intense competition. With consumers having more alternatives, their evaluations of products against their expectations or satisfaction levels increase competition. This study aims to determine whether there is an influence of price perception, taste, and service quality on customer satisfaction, using a quantitative research approach with an associative design. The sampling method employed in this research is nonprobability sampling with incidental sampling, involving 100 respondents. The analysis method utilizes partial least squares (PLS) with SmartPLS 3.2.9 software. The study findings reveal that price perception, taste, and service quality significantly and positively impact customer satisfaction.